Differentiating Charter Elementary Schools From Traditional Public Elementary Schools by Teacher Characteristics (Global Journal of Human-Social Science, 2017)
In this study the extent to which differences were present in teacher characteristics between charter elementary and traditional public elementary schools in Texas was addressed The Moreno and Slate 2016 study was replicated in this investigation to determine whether the percentage of beginning teachers continued to be the major school characteristic that most differentiated charter schools from traditional public schools Participants in this study were charter and traditional publicelementary schools in Texas in the 2014-2015 school year Canonical stepwise discriminant analyses were conducted to determine whether teacher characteristics i e base salary average teacher tenure average teacher experience beginning teachers teachers with no degree teachers with bachelor s degree teachers with master s degree teachers with doctoral degree Blackteachers Hispanic teachers male teachers and female teachers could differentiate charter elementary schools from traditional public elementary schools The canonical discriminant analysis revealed that the two school types could be statistically significantly differentiated with the percentage of beginning teachers again making the most important contribution to the group separation Charter elementary schools were more likely to have a higher percentage of beginning teachers Black teachers and teachers who did not have a college degree than were traditional public elementary schools Implications of the results and suggestions for future research are provided
Keywords: charter school; traditional public school; beginning teacher; experienced teacher; highly qualified teacher